Kinship System And City Identity: A Socio- Anthropological Approach In The City of Khenchela, Algeria - Mabrouki , Amar (Journal of Human Sciences, 2024)
The research aims to reveal the kinship system and its relationship with the city’s identity. This is a practical research, in which we relied on the descriptive approach, and the historical method has also been used to study the phenomenon in its historical context. For this, the interview was used as the main tool, as well as participant observation, with the help of informants, and images. The research yielded several results, the most important of which are:• Tribal membership appeared in newly built areas, causing a socio-tribal division of the city to the detriment of tools. Development planning and development strategies• -Commitment to the kinship system is stronger than commitment to duty and law.• The selection of people's representatives in local elections is controlled by tribal affiliation at the expense of parties and programs.• -Parental ties have affected the functions and identity of the city and produced a new model, which is the ruro-urban model.